Acute respiratory failure in children: epidemiological data from the Italian Network of Pediatric Intensive Care Units - Wolfer, A.; Iannella, E.; Gualino, et al., J. (Acta Biomedica Atenei Parmensis, 2012)
Introduction: observational prospective multicenter study to describe the incidence of ARF in Italian PICUs. Materials and Methods: all children aging 0-16 years admitted in 13 Italian PICUs over one year. Outcomes: 2267 children were analyzed. ARF is the most common reason for admission in PICUs and about one children over two receive mechanical ventilation. ALI/ARDS incidence is 6,5% with a mortality rate of 30%. Discussion/Conclusions: the incidence and mortality of ALI/ARDS in PICUs in Italy are similar to those published by other studies. Surfactant is still a promise therapy for children and should be investigated for its potential benefit.